2020
DOI: 10.1111/ijlh.13403
|View full text |Cite
|
Sign up to set email alerts
|

Further evaluation of the world health organization international reference reagent for Haemoglobin A2 measurement

Abstract: Introduction The accurate measurement of HbA2 is essential for the detection of β‐thalassaemia carriers and as no single calibrant is used by the various manufacturers of analysers, differences are seen in results obtained. The World Health Organization International Reference Reagent for HbA2 (WHO IRR 89/666) was made available to diagnostic laboratories in the 1980s and remains the only international reference material available. A previous study (2015) demonstrated that the WHO IRR remained suitable for use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
1
3
1
Order By: Relevance
“…This reflects our earlier results when we found A 2 by capillary electrophoresis to have a median of 2.65% in normal subjects while HPLC had a median of 2.77% ( p < 0.001). It also reflects the results observed by others for samples with a normal A 2 including a comparison of BioRad Variant II HPLC with Sebia Capillarys 2 capillary electrophoresis [ 4 ] and a recent study using three capillary electrophoresis methods and five HPLC methods [ 1 ]. However interestingly the first of these two studies found a lower haemoglobin A 2 by capillary electrophoresis when the haemoglobin A 2 was elevated as a result of β thalassaemia heterozygosity while the latter found no difference between these two technologies.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…This reflects our earlier results when we found A 2 by capillary electrophoresis to have a median of 2.65% in normal subjects while HPLC had a median of 2.77% ( p < 0.001). It also reflects the results observed by others for samples with a normal A 2 including a comparison of BioRad Variant II HPLC with Sebia Capillarys 2 capillary electrophoresis [ 4 ] and a recent study using three capillary electrophoresis methods and five HPLC methods [ 1 ]. However interestingly the first of these two studies found a lower haemoglobin A 2 by capillary electrophoresis when the haemoglobin A 2 was elevated as a result of β thalassaemia heterozygosity while the latter found no difference between these two technologies.…”
Section: Discussionsupporting
confidence: 85%
“…The diagnosis of β thalassaemia heterozygosity requires that quantification of haemoglobin A 2 is both precise (reproducible) and accurate (close to ‘truth’). The difference in mean values with different technologies that have previously been reported [ 1 ] and the difference in median values of normal samples observed in this study indicate that accuracy has not yet been achieved despite attempts at standardisation.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…(14) Furthermore, HbA2 <3.5% could have potentially been erroneously attributed to iron deficiency. (32) Low value of SLI or MI together with normal to borderline HbA2 levels might suggest an IDA or otherwise possible an α-thalassemia carrier. The possible α-thalassemia defect might be deletional or non-deletional α-globin, and therefore, need to be further analysed by molecular analysis.…”
Section: Discussionmentioning
confidence: 99%